2016
DOI: 10.3748/wjg.v22.i18.4585
|View full text |Cite
|
Sign up to set email alerts
|

Changes in patients’ symptoms and gastric emptying afterHelicobacter pyloritreatment

Abstract: FD patients have delayed gastric emptying. H. pylori infection treatment helps to improve symptoms of dyspepsia and is a reasonable choice for treatment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
4
16
0
1
Order By: Relevance
“…However, this study found that the H. pylori infection rate was higher in populations experiencing dyspeptic symptoms in recent years than in the normal population, which is consistent with the findings of many studies (31,32). However, it remains controversial whether the eradication of H. pylori infection could improve the symptoms of functional dyspepsia (33,34). In the future, the correlation between different digestive symptoms and H. pylori infection, as well as the improvement of digestive symptoms post-H. pylori eradication, may be further studied to clarify the correlation between H. pylori infection and gastrointestinal symptoms.…”
Section: Relationship Between Helicobacter Pylori Infection and Persosupporting
confidence: 91%
“…However, this study found that the H. pylori infection rate was higher in populations experiencing dyspeptic symptoms in recent years than in the normal population, which is consistent with the findings of many studies (31,32). However, it remains controversial whether the eradication of H. pylori infection could improve the symptoms of functional dyspepsia (33,34). In the future, the correlation between different digestive symptoms and H. pylori infection, as well as the improvement of digestive symptoms post-H. pylori eradication, may be further studied to clarify the correlation between H. pylori infection and gastrointestinal symptoms.…”
Section: Relationship Between Helicobacter Pylori Infection and Persosupporting
confidence: 91%
“…In our study, the number of periganglionic inflammatory Analytical Cellular Pathology cells was significantly increased in H. pylori-positive patients compared to controls. Although this is an unusual finding, as gastritis is basically a mucosal disease, myenteric plexitis might be hypothesized as responsible for gastric dysmotility frequently described in H. pylori-induced gastritis [4,28]. The immunohistochemical analysis of the myenteric infiltrate revealed a significant component of CD3-immunoreactive T cells, in agreement with previous reports showing that in inflammatory neuropathies there is a predominant T cytotoxic activity directed against proteins expressed by enteric neurons [18,22].…”
Section: Inflammation Of Myenteric Plexussupporting
confidence: 90%
“…Salicru et al [29] showed low prevalence of H. pylori infection in patients with gastroparesis. Zhang et al reported H. pylori treatment improved gastric emptying in FD patients [30]. The relationship between H. pylori infection and gastric emptying is controversial.…”
Section: Discussionmentioning
confidence: 99%